(t-2)(t+4)=0

Simple and best practice solution for (t-2)(t+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t-2)(t+4)=0 equation:



(t-2)(t+4)=0
We multiply parentheses ..
(+t^2+4t-2t-8)=0
We get rid of parentheses
t^2+4t-2t-8=0
We add all the numbers together, and all the variables
t^2+2t-8=0
a = 1; b = 2; c = -8;
Δ = b2-4ac
Δ = 22-4·1·(-8)
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-6}{2*1}=\frac{-8}{2} =-4 $
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+6}{2*1}=\frac{4}{2} =2 $

See similar equations:

| 7x+2=17-3x# | | 3x-5=2×+4 | | 9e-3/6=4 | | -12=-7x+16 | | (5d-5)(d+11)=0 | | l^2-12l+85=0 | | 8w-w^2-960^2=0 | | 28-x=30 | | 1/2(x+8)=x-2 | | -5y-2=18 | | 4x+5=-5-6 | | y=5000*1,03 | | l^2-52l+672=0 | | 5/7t5=2/7t14 | | -3x+22=x-14 | | -7=2+u/3 | | 19+8n=-15 | | 6(−2g−1)=−(13g+2)6(−2g−1)=−(13g+2) | | 3+5x=45 | | 6(10x-8)-2(5x-4)=-30 | | -2+n/5=5 | | H(x)=4^x | | x^2−12x+35=0 | | -20=-5(x-4) | | 2a-0.08a=2-a | | 5x-3(x+5)=-25 | | -2(3x-3)=42 | | 2x+3*(-3x/4-2)=-5 | | 4x-5=7# | | 7x+-9*2=5x+-6 | | 2/v-5=6/3v-15 | | 8x^2-12=7x^2-4x |

Equations solver categories